Spatio-Temporal Regulation of Gibberellin Biosynthesis Contributes to Optimal Rhizome Bud Development - Kanako Bessho-Uehara; Tomoki Omori; Stefan Reuscher; Keisuke Nagai; Ayumi Agata; Mikiko Kojima; Yumiko Takebayashi; Takamasa Suzuki; Hitoshi Sakakibara; Motoyuki Ashikari; Tokunori Hobo (Rice)
Abstract The perennial life cycle involves the reiterative development of sexual and asexual organs. Asexual structures such as rhizomes are found in various plant species, fostering extensive growth and competitive advantages. In the African wild rice Oryza longistaminata, we investigated the formation of rhizomes from axillary buds, which notably bend diagonally downward of the main stem, as the factors determining whether axillary buds become rhizomes or tillers are unclear. Our study revealed that rhizome buds initiate between the third and fifth nodes of seedlings beyond the 6-leaf stage, while the buds above the sixth node develop into tillers. We propose that precise regulation of gibberellin (GA) biosynthesis plays a pivotal role in optimal rhizome bud development, as demonstrated by a comparative transcriptome analysis between tiller buds and rhizome buds and quantification of phytohormones. Furthermore, GA4 treatment upregulated the expression of genes associated with flowering repression and cell wall modification. These findings highlight the integration of GA biosynthesis and flowering repression genes as crucial in asexual organ development, shedding new light on the molecular mechanisms governing rhizome bud development in O. longistaminata and deepening our understanding of asexual reproduction regulation in perennial plants.